Manichaean delirium : decolonizing the judiciary and Islamic renewal in Sudan, 1898-1985 - Ibrāhīm, ʻAbd Allāh ʻAlī (Islam in Africa, 2008)
Uses the concept of the "Manichaean" geography of the colony, popularized by Fanon, to account for the virulent Islamic renewal in Sudan. Focusing on the Sudan judiciary, characterized by an unrelenting rift between its civil and Sharia divisions, this book examines the various forces that sought to profit from these Manichaean resources.